A new pelagic predatory pike cichlid (Teleostei: Cichlidae: Crenicichla ) from the C. mandelburgeri species complex with parallel and reticulate evolution - Piálek, Lubomír (2019)
The Crenicichla mandelburgeri species complex from the Middle Parana shows parallel evolution of ecomorphs to the unrelated C. missioneira species complex from the Uruguay River. In this article, we describe a new species from the C. mandelburgeri species complex that has evolved a parallel morphology and ecology to an unrelated species from the C. missioneira species complex (C. celidochilus). The new species is a pelagic predator that feeds predominantly on fishes and together with C. celidochilus is the only known pelagic species in the large riverine genus Crenicichla. The new species is endemic solely to a small tributary (the Urugua-i) of the Middle Parana River where it is sympatric and partly syntopic with two other closely related endemic species that, however, differ strongly in their ecomorphologies (one is a generalistic invertivore and the other a specialized molluscivore). Mitochondrial DNA phylogeny finds the new species nested within the widespread C. mandelburgeri. Reduced genome-representation ddRAD analyses, however, demonstrate that this new species is of a hybrid origin and shares ancestry with C. ypo, one of the two studied sympatric species.